The Road to Opportunities in Rural India : The Economic and Social Impacts of PMGSY - Herrera Dappe, Matias; Alam, Muneeza Mehmood; Andres, Luis (World Bank, Washington, DC, 2021)
This report presents the results of an impact evaluation of the Pradhan Mantri Gram Sadak Yojana (PMGSY) rural roads program in India. The program targeted the provision of all-weather roads to about 178,000 habitations across India. The impact evaluation uses a difference-in-difference approach and panel data from the states of Himachal Pradesh, Madhya Pradesh, and Rajasthan collected in 2009 and 2017. The evaluation finds that PMGSY improved accessibility, particularly in hilly areas, increased access to economic opportunities, triggering a change in the structure of employment in rural India, and had a positive impact on human capital formation in rural India, with boys and girls benefiting equally.